Human anatomy and physiology - Marieb, Elaine N. R.N., Ph.D.; Hoehn, Katja M.D., Ph.D. (Harlow Pearson, 2019)
The eleventh global edition of Human Anatomy & Physiology offers the most effective approach to learning and teaching anatomy and physiology through these hallmark features: Chapter-opening roadmaps provide an overview of the key concepts in a chapter and show they are connected to each other; Career connection videos feature health care professionals who describe how the chapter content relates to their everyday work; Summary tables help students connect information and see the big picture; Focus figures and in-line figures illustrate complex concepts and enhance visual literacy; A huge range of self-assessment questions allow students to exercise critical thinking skills and prepare for tests; Homeostatic imbalance discussions and clinical case studies help students clinically apply the concepts they have learnt; Mastering A&P offers a wide range of teaching resources for instructors and allows students to be engaged in a continuous process of learning and assessment
1. The human body: an orientation -- 2. Chemistry comes alive -- 3. Cells: the living units -- 4. Tissue: the living fabric -- 5. The integumentary system -- 6. Bones and skeletal tissues -- 7. The skeleton -- 8. Joints -- 9. Muscles and muscle tissue -- 10. The muscular system -- 11. Fundamentals of the nervous system and nervous tissue -- 12. The central nervous system -- 13. The peripheral nervous system and reflex activity -- 14. The autonomic nervous system -- 15. The special senses -- 16. The endocrine system -- 17. Blood -- 18. The cardiovascular system: the heart -- 19. The cardiovascular system: blood vessels -- 20. The lymphatic system and lymphoid organs and tissues -- 21. The immune system: innate and adaptive body defenses -- 22. The respiratory system -- 23. The digestive system -- 24. Nutrition, metabolism, and energy balance -- 25. The urinary system -- 26. Fluid, electrolyte, and acid-base balance -- 27. The reproductive system -- 28. Pregnancy and human development -- 29. Heredity
Keywords: Human physiology; Human anatomy